Kawalerowie Orderu Uśmiechu spadkobiercami myśli „prawodzieckowej” Janusza Korczaka - Michalak, Marek (Pedagogika Społeczna Nova, 2022)
The aim of the article is to discuss the issues related to the development and continuation of Janusz Korczak’s ideas of the child and its due place in society, which were revolutionary at his time, based on the implementation of a project focused on children’s evaluation of adult’s positive work. In particular, the biographical statements of adults awarded the Order of the Smile were analyzed. The basic ques- tions, which guide the considerations undertaken here, relate to the analysis of the practical dimension of the Order of the Smile within Janusz Korczak’s pedagogy. The analysis of the biographies of the chosen Knights of the Order of the Smile was made according to Fritz Schütze’s theory, with the use of biographical process structures: action plans, institutional patterns of life course, trajectories and biographical metamorphoses.